Peran Profitability dan Capital Structure dalam Memengaruhi Firm Value - Zulkarnain Zulkarnain; Rida Farida (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2018)
This study aims to examine the effect of profitability and capital structure to firm value. Data collected from manufacturing company sub sector secondary of consumer goods industry listed in the Indonesia Stock Exchange in 2012-2016. The sample collection technique is carried out by using purposive sampling method. Based on the determined criteria, so the samples are 31 manufacturing companies sub sector secondary of consumer goods industry which have continuously published their financial annual report during the period of 2012-2016. The research hypothesis is performed by using multiple linear regressions analysis technique with the assistance of SPSS application version 20. The result of this study shows that profitability, represent by Return on Asset (ROA) has significant positive effect to the firm value, represent by Price to Book Value (PBV). Capital structure, represent by Debt to Equity Ratio (DER) on the other hand has insignificant negative effect to the firm value (PBV). The result of F test shows that simultaneously Return on Asset (ROA) and Debt to Equity Ratio (DER) has significant positive effect to firm value (PBV).